Early and delayed laparoscopic cholecystectomy in patients with acute cholecystitis - Alaubaidi, Tariq E. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: laparoscopic cholccystectomy (LC) gained a wide acceptance as treatment of choice for acute cholccyslitis (AC) as early in 72 hours of admission or after interval of 8-12 weeks after the patient treated by medical treatment.